Mo Single-Atom Nanozyme Anchored to the 2D N‑Doped Carbon Film: Catalytic Mechanism, Visual Monitoring of Choline, and Evaluation of Intracellular ROS Generation - Sun, Qijun; Xu, Xiaoyu; Liu, Song; Wu, Xinzhao; Yin, Chenhui; Wu, Meng; Chen, Yuxue; Niu, Na; Chen, Ligang; Bai, Fuquan (ACS applied materials & interfaces, 2023)
Single-atom nanozymes (SANs) have attracted great attention in constructing devices for instant biosensing due to their excellent stability and atom utilization. Here, Mo atoms were immobilized in 2D nitrogen-doped carbon films by cascade-anchored one-pot pyrolysis to obtain Mo single-atom nanozyme (Mo-SAN) with high atomic loading (4.79 wt %) and peroxidase-like activity. The coordination environment and enzyme-like activity mechanism of Mo-SAN were studied by combining synchrotron radiation and density functional theory. The strong oxophilicity of single-atom Mo makes the catalytic center more capable of transferring electrons to free radicals to selectively generate •OH in the presence of H2O2. Choline oxidase and Mo-SAN were used as signal opening unit and signal amplification unit, respectively. Combining the portability and visualization functions of smartphone and test strips, a paper-based visual sensing platform was constructed, which can accurately identify choline at a concentration of 0.5–35 μM with a limit of detection as low as 0.12 μM. The recovery of human serum samples was 96.4–102.2%, with an error of less than 5%. Furthermore, the potential of Mo-SAN to efficiently generate toxic •OH in tumor cells was intuitively confirmed. This work provides a technical and theoretical basis for designing highly active SANs and detecting neurological markers.